Effect of a dual orexin receptor antagonist on Alzheimer's disease: Sleep disorders and cognition - Zhou, Mengzhen; Tang, Shi (Frontiers in Medicine, 2023)
Orexin is a neuropeptide produced by the lateral hypothalamus that plays an important role in regulating the sleep-wake cycle. The overexpression of the orexinergic system may be related to the pathology of sleep/wakefulness disorders in Alzheimer's disease (AD). In AD patients, the increase in cerebrospinal fluid orexin levels is associated with parallel sleep deterioration. Dual orexin receptor antagonist (DORA) can not only treat the sleep-wakefulness disorder of AD but also improve the performance of patients with cognitive behavior disorder. It is critical to clarify the role of the orexin system in AD, study its relationship with cognitive decline in AD, and evaluate the safety and efficacy of DORA.